The COVID‐19 infection control response at a large stand‐alone comprehensive cancer center in Los Angeles County. Issue 1 (1st July 2022) - Battey, Hannah; Doran, Brenna; Flood, Annemarie; Nussbaum, Juliet; Seto, Tyler; Srisatidnarakul, Suwannee; Tegtmeier, Bernard; Dadwal, Sanjeet
Abstract: Background: The City of Hope National Medical Center (COH) is the only stand‐alone comprehensive cancer center in Los Angeles, a county that was deemed a COVID‐19 pandemic epicenter at the height of the 2020 winter surge. The immunocompromised patient population frequently experienced delays in infection control guidelines from local and government bodies due to minimal data available in comparison to the general population. This required COH to make swift, informed decisions for the best interest of the patient population. Aim: Here, we review the comprehensive COVID‐19 infection control response conducted at COH within the context of a high‐risk patient population, predominately comprised of patients with hematologic malignancies. Methods and Results: This infection control response focused on prevention of COVID‐19 transmission on campus, COVID‐19 testing, and isolation management. These efforts consisted of COVID‐19 screening, limitation of personnel on campus, source control, contact tracing, COVID‐19 vaccination, establishment of in‐house testing and implementation and management of COVID‐19 testing. Between January 2020 and September 2021, COH implemented a robust in‐house testing program, completed well over 1000 contact traces, ensured COVID‐19 vaccinations were distributed to all eligible staff and patients, and established an algorithm for COVID‐19 infection resolution, all without compromising the number of hematopoietic stem cell transplants (HCTs) performed, surgical volume, or healthcare‐associated standardized infection ratios (SIR). Conclusion: Institutional collaboration and attention to infection control was pivotal to minimizing the burden of the COVID‐19 pandemic.